Uczniowie szkół Komisji Edukacji Narodowej w Wielkopolsce w świetle źródeł - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2024)
Although education in Greater Poland had been already well-organized in the late Middle Ages, curricula are known, sometimes also the names of the teachers, and information about the students is sporadic and recorded only in court records. It was not until the creation of a state school authority, the Commission of National Education, triggered off creation of documentation that allows to capture information about the fate of individual students. The aim of this article is to show the possibilities for studying the student environment of schools of the Commission of National Education in Greater Poland form the point of view of the sourcea. Valuable information on the functioning of public schools is provided by the reports of the inspectors-general; it was the main source of information for the Commission, alongside the reports sent by the schools. Relatively recently developed materials from the collections of the Archdiocesan Archives in Poznań were also used.